Menganalisis Tantangan Komunikasi Bisnis dalam Lingkungan Lintas Budaya - Sefthian Sefthian; Aulia Rizka (Yayasan Aya Sophia Indonesia, 2025)
Globalization we live in today hasencouraged cross-border business interactions, making crosscultural communication a critical aspect of organizational success.This paperaims to comprehensively analyze the variousbusiness communication challenges that arise due to cultural differences. This researchidentifies and explores key challenges such as language differences, cultural values and norms, stereotypes, stnosetism,business communication contexts, decision-making processes and business ethics. Through aliterature review and conceptual analysis, this research aims to analyze the significantimpact of these challenges on the effectiveness of collaboration, negotiation and international business relationship building. It further provides practical implications and strategic recommendations for organizations to increase cultural awareness, enhance cultural insights and adopt adaptive communication practices to avoid the risk of misunderstandings and enhance success in a diverse global business environment. The research also highlights the negative consequences of failed, cross-cultural communication, including misunderstood conflicts and potential financial losses. Furthermore, the research offers a strategic framework and practical recommendations for organizations to minimize the challenges that will be faced, these strategies recommended include increasing employee cultural awareness. Adaptation of communication styles, building strong relationships, and utilizing resources such as translators and cultural mediators. In conclusion, this study explains that effective navigation within the scope of cross-cultural business communication, the development of intercultural competence and the implementation of adaptive and sensitive communication differences. By adopting a proactive approach, organizations can improve communication effectiveness, strengthen international business relationships and be able to compete in the global market.